AVANSUS Extension Project: Right health, citizenship and its interfaces - Pereira dos Santos, Wallison; Bernardo de Lima, Gigliola Marcos (Guará Journal, 2018)
The University Extension is the great key to the university's approximation with the local community, in order to contribute to the formation of citi-zenship and dissemination of knowledge. The objective is to present the experience acquired from the experience as a grant holder of the exten-sion project and provide information for the construction of new exten-sion projects in a wide range of fields. It is characterized as a descriptive, qualitative  study  in  the  modality  of  experience  reporting,  experienced  by  the  scholarship  student  of  the  Extension  Project  "AVANSUS",  Federal  University of Campina Grande, Campus Cuité-PB. The results were orga-nized into three categories, namely: Construction and application of the board to the community; Experience as a project grantee; Impacts of the AVANSUS project. Through the results obtained in the present study, it is clear  that  the  project  reached  the  proposed  objectives  and  effectively  contributed  to  the  rapprochement  between  the  local  community  and  the university.
Keywords: University extension; Right to health; Citizenship; Playful